Chemotherapeutic treatment of acute myeloid leukemia: incorporating the results of recent clinical trials. (January 2015) - Mahdi, Ali J; Mahdi, Eamon J; Knapper, Steven
Better outcomes for patients with acute myeloid leukemia over the last 30 years have been largely achieved by improvements in supportive care measures rather than therapeutic advances. The combination of daunorubicin and cytarabine has remained the standard of care for patients undergoing intensive induction–consolidation treatment. In less fit older patients, low-dose cytarabine is the equivalent, although the hypomethylating agent azacitidine may be challenging current practice. Enhanced understanding of disease pathogenesis and therapy resistance has enabled the entry of novel chemotherapeutic and nonchemotherapeutic agents into clinical development with varied levels of activity. This article examines the evidence behind established chemotherapy practices for intensive and nonintensive acute myeloid leukemia treatments with an emphasis on emerging clinical trial data from novel chemotherapeutic and nonchemotherapeutic agents.